Antifungal Potential of Biogenic Zinc Oxide Nanoparticles for Controlling Cercospora Leaf Spot in Mung Bean - Zill-e-Huma Aftab; Faisal Shafiq Mirza; Tehmina Anjum; Humaira Rizwana; Waheed Akram; Muzamil Aftab; Muhammad Danish Ali; Guihua Li (Nanomaterials)
Agricultural growers worldwide face significant challenges in promoting plant growth. This research introduces a green strategy utilizing nanomaterials to enhance crop production. While high concentrations of nanomaterials are known to be hazardous to plants, this study demonstrates that low doses of biologically synthesized zinc oxide nanoparticles (ZnO NPs) can serve as an effective regulatory tool to boost plant growth. These nanoparticles were produced using Nigella sativa seed extract and characterized through UV-Vis spectroscopy, FT-IR, X-ray diffraction, and scanning electron microscopy (SEM). The antifungal properties of ZnO NPs were evaluated against Cercospora canescens, the causative agent of Cercospora leaf spot in mung bean. Application of ZnO NPs significantly improved plant metrics, including shoot, root, pod, leaf, and root nodule counts, as well as plant length, fresh weight, and dry weight—all indicators of healthy growth. Moreover, low-dose ZnO NPs positively influenced enzymatic activity, physicochemical properties, and photosynthetic parameters. These findings suggest that biologically synthesized ZnO NPs offer a promising approach for enhancing crop yield and accelerating plant growth.